Neonatal Cholestasis - Differential Diagnoses, Current Diagnostic Procedures, and Treatment - Goetze, Thomas; Blessing, Holger; Grillhösl, Christian; Gerner, Patrick; Hoerning, Andre (Frontiers in Pediatrics, 2015)
Cholestatic jaundice in early infancy is a complex diagnostic problem. Misdiagnosis of cholestasis as physiologic jaundice delays the identification of severe liver diseases. In the majority of infants, prolonged physiologic jaundice represent benign cases of breast milk jaundice, but few among them are masked and caused by neonatal cholestasis (NC) that requires a prompt diagnosis and treatment. Therefore, a prolonged neonatal jaundice, longer than 2 weeks after birth, must always be investigated because an early diagnosis is essential for appropriate management. To rapidly identify the cases with cholestatic jaundice, the conjugated bilirubin needs to be determined in any infant presenting with prolonged jaundice at 14 days of age with or without depigmented stool. Once NC is confirmed, a systematic approach is the key to reliably achieve the diagnosis in order to promptly initiate the specific, and in many cases, life-saving therapy. This strategy is most important to promptly identify and treat infants with biliary atresia, the most common cause of NC, as this requires a hepatoportoenterostomy as soon as possible. Here, we provide a detailed work-up approach including initial treatment recommendations and a clinically oriented overview of possible differential diagnoses in order to facilitate the early recognition and a timely diagnosis of cholestasis. This approach warrants a broad spectrum of diagnostic procedures and investigations including new methods that are described in this review.
EVALuna2:18888